2015
DOI: 10.1016/j.topol.2015.05.070
|View full text |Cite
|
Sign up to set email alerts
|

A group topology on the real line that makes its square countably compact but not its cube

Abstract: Under p = c, we show that it is possible to endow the additive group of the real line with a Hausdorff group topology that makes its square countably compact but not its cube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We prove (#). All numbered references in this proof are from the paper A. H. Tomita, 2015. First, notice that if ([ℎ 𝑖 ]  ∶ 𝑖 < 𝑚) is a ℚ-linearly independent family and the group generated by it does not contain nonzero constant classes, the it satisfies the conclusion of Lemma 4.1. Then, following the proof of Lemma 7.1, using the 𝑓 's as the ℎ's themselves, we see that the functions ℎ 𝑖 for 𝑖 < 𝑚 are integer combinations of the stack 1 𝑁  that was constructed.…”
Section: Proof Of Lemma 346mentioning
confidence: 99%
See 1 more Smart Citation
“…We prove (#). All numbered references in this proof are from the paper A. H. Tomita, 2015. First, notice that if ([ℎ 𝑖 ]  ∶ 𝑖 < 𝑚) is a ℚ-linearly independent family and the group generated by it does not contain nonzero constant classes, the it satisfies the conclusion of Lemma 4.1. Then, following the proof of Lemma 7.1, using the 𝑓 's as the ℎ's themselves, we see that the functions ℎ 𝑖 for 𝑖 < 𝑚 are integer combinations of the stack 1 𝑁  that was constructed.…”
Section: Proof Of Lemma 346mentioning
confidence: 99%
“…In A. C. Boero and A. H. Tomita, 2010, such a topology was constructed using c selective ultrafilters. In A. Boero et al, 2015, it is shown that there is a group topology without non-trivial convergent sequences such that ℝ 2 is countably compact, a first step to make larger powers of ℝ countably compact.…”
Section: Introductionmentioning
confidence: 99%